MEMAHAMI MAKNA KOMUNIKASI SIMBOLIK TRADISI ADAT ISTIADAT MARAPU DALAM PERKAWINAN MASYARAKAT SUMBA DI DESA KATIKU LUKU KECAMATAN MATA WAI LA PAWU KABUPATEN SUMBA TIMUR - Adi Novayanti, Ni Made; David Frids Nggala Lili (Jurnal Kajian Ilmu Komunikasi, 2021)
In a study entitledâ€ Understanding The Meaning of Sombolic Communication, The Marapu Customs and Traditions in Sumbanese Marriages in KatikuLuku Village, Mata Wai La Pawu District, East Sumba Regencyâ€aims to find out about these traditional traditions si a matterof interest in understanding the meaning and traditions of these costoms, of course there is something that must be concluded to be an indispenseble value and the benefits and need to be considered. One that must be maintained is the common sense of the community so that it si able to maintain and be preserved and as a broad insight to be maintained and maintained. Based on the results ofthe study, it is known that there is significant support between the community andtraditional leaders by maintaining traditonal kustoms in katiku luku village. is a from of loyalty and to continusly maintain these traditions, of course theres is cooperation between adat and the katiku luku village community as a from of authoryty for the community. Understanding The Meaning of Sombolic Communication, The Marapu Customs and Traditions in Sumbanese Marriages in KatikuLuku Village, Mata Wai La Pawu District, East Sumba Regency